النظام القانوني لشركات التأمين وإعادة التأمين في التشريع الجزائري - سالمة مرازقة; نجيبة رجايمية (My University, 2026)
Abstract This study examines the legal framework governing insurance and reinsurance companies under Algerian legislation. It aims to identify the legislative and regulatory framework governing these companies since the issuance of Ordinance No. 95-07 relating to insurance and the amendments introduced thereto, in addition to the various executive decrees and ministerial decisions regulating this vital economic sector. The importance of this topic lies in the fact that the insurance sector constitutes a fundamental pillar of the financial and economic system of any state, as it provides protection for individuals and institutions against various risks, while also contributing to the mobilization of national savings and directing them toward investment. This study is divided into two main chapters. The first chapter addresses the establishment of insurance and reinsurance companies and the conditions governing the exercise of their activities, whereas the second chapter focuses on the system of supervision and control over these companies and the legal protection mechanisms established for them. .......................... الملخص تتناول هذه الدراسة النظام القانوني لشركات التأمين وإعادة التأمين في التشريع الجزائري، وتسعى إلى الكشف عن الإطار التشريعي والتنظيمي الذي يحكم هذه الشركات منذ صدور الأمر رقم 95-07 المتعلق بالتأمينات وما طرأ عليه من تعديلات، مرورًا بمجموعة من المراسيم التنفيذية والقرارات الوزارية المنظِّمة لهذا القطاع الاقتصادي الحيوي. وتبرز أهمية هذا الموضوع من كون قطاع التأمين يُعدّ ركيزةً أساسية في المنظومة المالية والاقتصادية لأيّ دولة، إذ يوفر الحماية للأفراد والمؤسسات من المخاطر المختلفة، ويُسهم في تعبئة المدخرات الوطنية وتوجيهها نحو الاستثمار. تنقسم هذه الدراسة إلى فصلين رئيسيين: يتناول الفصل الأول تأسيس شركات التأمين وإعادة التأمين وشروط ممارسة نشاطها، فيما يُعنى الفصل الثاني بنظام الرقابة والإشراف على هذه الشركات وآليات الحماية القانونية المقررة. .......................... Résumé Cette étude examine le régime juridique des sociétés d'assurance et de réassurance en droit algérien. Elle analyse le cadre législatif et réglementaire issu de l'Ordonnance n° 95-07 relative aux assurances et ses textes d'application, notamment les conditions de constitution d'agrément et de contrôle de ces sociétés. L'étude met en lumière les mécanismes de protection des assurés et les garanties de solvabilité imposées aux opérateurs du secteur
Keywords: Keywords: Insurance companies; reinsurance; licensing; administrative supervision; financial solvency.; الكلمات المفتاحية: شركات التأمين، إعادة التأمين، الاعتماد، الرقابة الإدارية، الملاءة المالية.; Mots-clés: Sociétés d'assurance; réassurance; agrément; contrôleadmin istratif; solvabilité; assurance obligatoire; droit algérien